Treatment of Advanced Melanoma in 2020 and Beyond - Jenkins, Russell W; Fisher, David E (Journal of investigative dermatology, 2021)
The melanoma field has seen an unprecedented set of clinical advances over the past decade. Therapeutic efficacy for advanced or metastatic melanoma went from being one of the most poorly responsive to one of the more responsive. Perhaps most strikingly, the advances that transformed management of the disease are based upon modern mechanism-based therapeutic strategies. The targeted approaches that primarily suppress the BRAF oncoprotein pathway have a high predictability of efficacy although less optimal depth or durability of response. Immunotherapy is primarily based on blockade of one or two immune checkpoints and has a lower predictability of response but higher fractions of durable remissions. This article reviews the clinical progress in management of advanced melanoma and also discusses the impact of the same therapies on earlier stage disease, where the agents have shown significant promise in treating resectable but high-risk clinical scenarios. Collectively, the progress in melanoma therapeutics has transformed the standard of care for patients, informed new approaches that are increasingly utilized for treatment of other malignancies, and suggest novel strategies to further boost efficacy for the many patients not yet receiving optimal benefit from these approaches.